2013
DOI: 10.2500/aap.2013.34.3678
|View full text |Cite
|
Sign up to set email alerts
|

Total IgE at 6 months predicts remittance or persistence of atopic dermatitis at 14 months

Abstract: Some patients with infantile atopic dermatitis (AD) achieve remission around 1 year old, but in others it persists. The difference between them is unclear. We performed a birth cohort study to find the markers predicting the outcome of infantile AD. We followed up a cohort (n = 314) from birth to 14 months of age, and cord blood was taken from the participants. Some of them (n = 144) had a physical examination and a blood test at 6 and 14 months of age. The subjects who had AD at 6 months (n = 34) were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…8 In addition, Kawamoto et al have more recently shown that egg white IgE sensitization at 6 months in infants with AD is significantly associated with more persistent AD. 10 These observations are consistent with the notion that the subgroup of AD infants with food IgE sensitization may be predisposed to involve a more T helper 2-biassed adaptive immunity in cutaneous inflammation. This is supported by the current observation that IgE sensitization to egg white is strongly associated with IgE sensitization to staphylococcal superantigens in older children with AD.…”
Section: Allergy and Asthma Proceedingssupporting
confidence: 80%
“…8 In addition, Kawamoto et al have more recently shown that egg white IgE sensitization at 6 months in infants with AD is significantly associated with more persistent AD. 10 These observations are consistent with the notion that the subgroup of AD infants with food IgE sensitization may be predisposed to involve a more T helper 2-biassed adaptive immunity in cutaneous inflammation. This is supported by the current observation that IgE sensitization to egg white is strongly associated with IgE sensitization to staphylococcal superantigens in older children with AD.…”
Section: Allergy and Asthma Proceedingssupporting
confidence: 80%
“…6,23,28,31,44,45,48 The duration of AD persistence was significantly higher in females (median: 9.0 years; mean ± SE: 12.7 ± 0.2 years) compared with males (median: 7.0 years; mean±SE: 11.7 ± 0.2 years) (HR 1.15; 95% CI 1.04-1.27; P = .006) (Fig 2, E).…”
Section: Ad Persistence By Gendermentioning
confidence: 90%
“…After review of the titles and abstracts, 9326 were excluded; an additional 634 articles were excluded after full-text review. In total, 46 studies were included in the review, of which 44 had valid frequency data that could be pooled, 7 had valid data to assess the effects of gender, 6,23,28,31,44,45,48 6 for allergen sensitization, 6,17,23,36,40,45 and 3 for baseline AD severity 17,28,40 on disease persistence. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram is presented in Fig 1. …”
Section: Literature Searchmentioning
confidence: 99%
“…We conducted the Gifu Allergy and Immunology Cohort Study (GAICS) (UMIN‐CTR registration number: UMIN000002926) , the details of which are described elsewhere . Written informed consent and CB samples were obtained at the time of birth.…”
Section: Methodsmentioning
confidence: 99%